The Impact of Work Discipline, Work Environment, and Emotional Intelligence on Employee Performance at the Civil Service Police Unit and Fire Department of Klungkung Regency - Yuni Pranatita (Jurnal Dialektika: Jurnal Ilmu Sosial, 2024)
Regional Government has a very important role and position, especially in providing good Public Services which must be supported by the role of Civil Servants because Civil Servants are in an effort to achieve national goals so that government officials must have good performance, so the problem can be formulated in research This is whether work discipline, work environment and emotional intelligence influence the performance of Civil Service Police Unit Employees in the Civil Service Police Unit and the Klungkung Regency Fire Department. Data collection in this research was carried out by means of documentation, observation, interviews and questionnaires with 127 people. The collected questionnaires were then analyzed using the Structure Equation Model (SEM). The results of the first hypothesis test show that there is a positive and significant influence between work discipline on the performance of Civil Service Police Unit employees. The results of the second hypothesis test show that there is a positive and significant influence between the work environment on the performance of Civil Service Police Unit employees. The results of the third hypothesis test show that there is a positive and significant influence between emotional intelligence on the performance of Civil Service Police Unit employees. Based on the calculation results, it shows that work discipline, work environment and emotional intelligence have a positive effect on the performance of Civil Service Police Unit employees in the Klungkung Regency Civil Service Police and Fire Department Units.